Exploring the Users’ Intention to Use Online Hospital Service Platform Based on Extend UTAUT - Qin, Peng; Yang, Hongmei; Jiang, Songyu (Migration Letters, 2023)
The online hospital service platform (OHP) has the potential to address the societal dilemma of inadequate and uneven distribution of medical resources. However, users exhibit a relatively low intention to use the platform. This study aims to integrate the Unified Theory of Acceptance and Use of Technology (UTAUT), the Health Belief Theory (HBT), and the Information System Success Mode (ISSM) to explore the factors influencing users’ intention to use OHP. A total of 503 valid responses were collected from Sichuan Province, China, and an empirical test was conducted using a structural equation model. The results indicate that the research model accounts for 57.8% of the variance in users’ intention to use OHP. Facilitating conditions, performance expectancy, and effort expectancy significantly and positively influence users’ intention to use OHP. Furthermore, system quality, information quality, and service quality significantly impact users’ intention to use OHP through both effort expectancy and performance expectancy. However, distinct from previous research, it is noted that social influence factors on users’ intent to use does not exhibit significance.